De se a (vo)cê: o percurso da indeterminação no Português brasileiro - Assis, Jacqueline de Sousa Borges de. (2017)
Considering the alterations in the grammar of PB as symptoms of the remarking of the Null Subject Parameter - PSN that the language has passed, I investigate the emergence of the 2nd person pronoun with generic mark-up, widely used in the spoken language as an alternative form to the pronouns: null non referential and generic, se , nós and a gente This thesis is based on the hypothesis that vocêgen is used on the function of indeterminating pronoun like the clitic se, whose deletion leaves this position empty or is substituted by vocêgen. I associate this possibility with the syntactic changes processed in PB: deletion of clitic se; emergence of the nominative weak pronoun paradigm in place of the pronominal Agr system as compensation for the loss of the referential null subject (Kato, 2000); loss of the property of genericity of the pronoun a gente ; emergence of existential constructions with ter ; tendency to fill the position of subject that moves to the loss of the non referential and generic null, in clear evidence of the linguistic embedding of the variation. The theoretical-methodological model followed is that of Parametric Sociolinguistics proposed by Kato & Tarallo (1989). Thus, in view of the interlinguistic variation, this thesis adopt as guiding principle Chomsky's grammatical theory of Principles & Parameters (1981), and advances of this theory in its minimalist version (Kato, 2000; Holmberg, 2010). The relevant point of this work in relation to the implementation of vocêgen is in the proposition that the interior of INFL is the locus where the pronoun is initially inserted before being moved to the position of grammatical subject of the constructions of terex in which the pronoun does not establish thematic relation with the verb. Considering the parametric variation, a comparative study with the EP proves that in relation to the performance of indefinite subjects, BP and PE also exemplify relevant contrasts, confirming the hypothesis that the syntactic changes that are triggering alteration of the PNS value is a phenomenon that affects only PB.